Genome- and Proteome-Wide Analysis of Lysine Acetylation in Vibrio vulnificus Vv180806 Reveals Its Regulatory Roles in Virulence and Antibiotic Resistance - Pang, Rui; Li, Ying; Liao, Kang; Guo, Penghao; Li, Yanping; Yang, Xiaojuan; Zhang, Shuhong; Lei, Tao; Wang, Juan; Chen, Moutong; Wu, Shi; Xue, Liang; et al. (Frontiers in Microbiology, 2020)
Infection with Vibrio vulnificus is notorious for its atypical clinical manifestations and irreversible disease progression. Lysine acetylation is a conserved post-translational modification that plays a critical regulatory role in diverse cellular processes. However, little is known about the role of lysine acetylation on the pathogenesis of V. vulnificus. Here, we report the complete genome sequence and a global profile for protein lysine acetylation of V. vulnificus Vv180806, a highly cefoxitin resistant strain isolated from a mortality case. The assembled genome comprised two circular chromosomes and one circular plasmid; it contained 4,770 protein-coding genes and 153 RNA genes. Phylogenetic analysis revealed genetic homology of this strain with other V. vulnificus strains from food sources. Of all the proteins in this strain, 1,924 (40.34%) were identified to be acetylated at 6,626 sites. The acetylated proteins were enriched in metabolic processes, binding functions, cytoplasm, and multiple central metabolic pathways. Moreover, the acetylation was found in most identified virulence factors of this strain, suggesting its potentially important role in bacterial virulence. Our work provides insights into the genomic and acetylomic features responsible for the virulence and antibiotic resistance of V. vulnificus, which will facilitate future investigations on the pathogenesis of this bacterium.